Pelayanan Pastoralia Transformatif untuk Penanganan Masalah Kekerasan Seksual Terhadap Perempuan di Ambon - Juliana Agusthina Tuasela; Yohanes Parihala (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
This study is based on the fact that there are many problems of sexual violence against women in Indonesia in general, and in Ambon city in particular. The list of female violence in Indonesia is increasing significantly every year, both published and unpublished because of the hidden culture. This study aims to reveal the data of sexual violence occurring in urban communities, particularly Ambon, Desa Passo, and to find out the tragic stories experienced by victims, and to describe a transformative pastoral approach that can be conducted by the church to assist victims, as well as make awareness the perpetrators of the violence against women, which is not in accordance to the will of God. The study uses qualitative research methods and interview techniques as a means of gathering information/data to achieve research objectives. This study found that cases of violence against women tended to increase, and victims often silenced the case because of the culture of shame (hidden culture) to hide cases of violence in order not to be known by others. It is also the reason how the difficulty for law enforcement to the crime. Therefore, it needs a transformative pastoral approach to free the victims from the hidden culture and affirming the existence of the victim so that they can be healed from a prolonged traumatic experience.